Femtosecond-laser-inscribed cladding waveguides in KTiOPO4 crystal for second-harmonic generation and Y-branch splitters - Li, Shi-Ling; Song, Yan; Ma, Li-Nan; Wang, Hai-Long (Frontiers in Physics, 2024)
In this study, the fabrication of straight-and Y-branch-cladding waveguides in KTiOPO4 crystals using femtosecond laser-direct writing is described. The second-harmonic generation (SHG) of green light through the cladding waveguides was realized using a pulsed-wave pump at 1064 nm. The guiding properties of straight-cladding waveguides fabricated by varying the laser-writing conditions were investigated. The minimum insertion loss was approximately 2.0 dB at 1064 nm. Confocal micro-Raman spectroscopy was used to investigate the lattice micro-modifications. The maximum SHG conversion efficiency of the straight-cladding waveguide reached 31.4% with a maximum output power of 79.29 mW from an input power of 252.6 mW. The performances of the Y-branch splitters with splitting angles ranging from 0.5°-2.6°were characterized at 1064 nm, showing excellent properties, including symmetrical output ends and approximately equal splitting ratios. An SHG conversion efficiency of 13.4% and maximum output power of 33.63 mW were achieved in the Y-branch splitter with a splitting angle of 1.0°. These findings support potential applications in constructing compact-frequency converters by using femtosecond laser-written KTiOPO4 depressed-cladding waveguides.